Global Sustainability Standards: A Competitive Framework for Future Economies - Dwiyanti, Andi Amytia Resty; Aryani, Irma (Journal of Indonesian Scholars for Social Research, 2025)
This research explores the relationship between sustainable economic practices and global competitiveness, with a particular focus on Indonesia’s economic landscape. As the global economy transitions towards environmentally sustainable and socially responsible business models, countries that integrate Environmental, Social, and Governance (ESG) standards into their policies gain a competitive advantage in international trade and investment. Indonesia, a resource-rich developing economy, faces both opportunities and challenges in aligning with global sustainability frameworks. The study analyzes Indonesia’s economic performance, trade policies, and sustainability initiatives, highlighting key factors such as GDP growth projections, foreign direct investment (FDI) trends, renewable energy adoption, and the impact of global environmental regulations. Findings indicate that Indonesia’s economic resilience remains strong, with a projected GDP growth of 5.2% in 2025. However, challenges persist, particularly reliance on fossil fuels (coal accounting for 60% of energy consumption), deforestation concerns in the palm oil industry, and gaps in policy enforcement. To remain globally competitive, Indonesia must accelerate its transition to a low-carbon economy, strengthen sustainability regulations, enhance corporate ESG adoption, and expand green investment initiatives. The study concludes that Indonesia’s long-term economic growth depends on its ability to balance sustainability with industrial and financial development. By fostering renewable energy innovation, circular economy strategies, and sustainable trade policies, Indonesia can secure a resilient and competitive position in the global market while achieving environmental and social progress.